Fábricas de software e a academia: análise da formação acadêmica em informática no município do Rio de Janeiro - Vivacqua, Flavio Ribeiro (2009)
As Brazil wants to be perceived as a competitor in providing computer applications and system development services in the global market, the concept of Software Factory gains importance. The metaphor for the 'Factory', when applied to the activity of software development, is used to describe organizations which produce software with a minimum quality standard and at competitive costs. However, the term 'Factory' recalls Fordist concepts, which have been challenged for a few decades in the manufacturing industry. This study analyzed university curricula and how students and teachers perceive the concept of Software Factory and assessed them in relation to the Fordism ------------ post-Fordism /continuum/. It was observed that some of the teachers who have influence over curricula define Software Factories according to Fordist concepts. It was also observed that, despite opportunities for improvements, curricula are adequately structured with regards to the skills a professional at these organizations must possess. We conclude that education provided at the programs being analyzed is adequate, but that it must be supplemented by companies or by the professionals themselves so that the knowledge acquired in the programs may be put in practice.